026 Dimensional flow cardiovascular magnetic resonance: two-centre, 1.5t, phantom and in-vivo validation study. (3rd April 2017) - Garg, Pankaj; Westenberg, Jos JM; Boogaard, Pieter J van den; Swoboda, Peter P; Aziz, Rahoz; Foley, James RJ; Fent, Graham J; Tyl, FGJ; Coratella, L; ElBaz, Mohammed SM; Geest, RJ van der; Higgins, David M; et al.
Abstract : Background: Validation of four-dimensional (4D) flow CMR accelerated acquisition methods is needed to make them more robust for clinical applications. 1 Our aim was to compare three widely-used acceleration methods in 4D flow CMR: 4D segmented fast-gradient-echo (4D- turbo-field-echo, 4D-TFE), 4D non-segmented gradient-echo with echo-planar imaging (4D- EPI) and 4D- k-t Broad-use Linear Acquisition Speed-up Technique accelerated TFE (4D- k-t BLAST). Methods: CMR was performed in two institutions on identical 1.5T systems. Acceleration methods were compared in static/pulsatile phantoms (Figure 1 ) and 25 volunteers. In volunteers, the CMR protocol included: cines, 2D phase contrast (PC) at the aortic valve (AV) and mitral valve (MV) and three whole-heart free-breathing (no respiratory motion correction) 4D flow CMR pulse sequences. Field-of-view, slices, phases (30), voxel size and VENC were the same for each subject. In volunteers, net acquisition time for each 4D flow sequence was recorded, as well as a visual grading of image quality on a four-point scale: 0, no artefacts to 3, non-evaluable. Results: For the pulsatile phantom experiments, the mean error against the reference flow by time beaker measurements for 4D-TFE was 4.9%±1.3%, for 4D-EPI 7.6%±1.3% and for 4D- k-t BLAST 4.4%±1.9%. In vivo, acquisition time was shortest for 4D-EPI at 7 min59s±2 min30s. 4D- EPI and 4D- k-t BLAST had minimal artefacts, while for 4D-TFE, 40% of AV and MV assessments were non-evaluable because of phase dispersion artefacts. Peak velocity assessment using 4D-EPI demonstrated best correlation to 2D PC (AV: r=0.78, p<0.001; MV: r=0.71, p<0.001). Coefficient of variability (CV) for net forward flow (NFF) volume was least for 4D-EPI (7%) (2D PC:11%, 4D-TFE: 29%, 4D- k-t BLAST: 30%, respectively) (Figure 2, 3 ). Conclusion: Of the three 4D flow CMR methods tested, 4D-EPI demonstrated the least susceptibility to artefacts, good image quality, modest agreement with the current reference standard for peak intra-cardiac velocities and the highest consistency of intra-cardiac flow quantifications. Competing interests: The authors declare that they have no competing interests. Acknowledgement: We thank Gavin Bainbridge, Caroline Richmond, Margaret Saysell and Petra Bijsterveld for their invaluable assistance in recruiting and collecting data for this study. Funding Sources: This work was supported by the British Heart Foundation [FS/10/62/28409 to S.P.] and Dutch ZonMw [Project Number: 104003001 to J.W]. References: . Dyverfeldt P, Bissell M, Barker AJ, Bolger AF, et al. 4D flow cardiovascular magnetic resonance consensus statement. J Cardiovasc Magn Reson2015;17:72.